Aeroelastic analysis of pre-stressed variable stiffness composite panels. (31st December 2019) - Rasool, Mehnaz; Singha, Maloy K
The effect of in-plane stresses on the stability behaviors of constant stiffness and variable stiffness composite panels, exposed to aerodynamic pressure, is studied using the finite element method. The dynamic pressure from the high velocity airflow is evaluated from the first-order piston theory, and the eigenvalue analysis is performed to investigate the flutter or divergence type of instabilities in such composite panels under combined mechanical and aerodynamic loads. Attempt is made to understand the effect of the lamination parameter on the stability characteristics of edge-supported and cantilever composite trapezoidal panels. Finally, the limit cycle oscillation of variable stiffness plates subjected to aerodynamic pressure is investigated.